YopJ targets TRAF proteins to inhibit TLR-mediated NF-kappaB, MAPK and IRF3 signal transduction - Sweet, Charles R; Conlon, Joseph; Golenbock, Douglas T; Goguen, Jon; Silverman, Neal (Cellular microbiology, 2007)
The Yersinia pestis virulence factor YopJ is a potent inhibitor of the NF-kappaB and MAPK signalling pathways, however, its molecular mechanism and relevance to pathogenesis are the subject of much debate. In this report, we characterize the effects of this type III effector protein on bone fide signalling events downstream of Toll-like receptors (TLRs), critical sensors in innate immunity. YopJ inhibited TLR-mediated NF-kappaB and MAP kinase activation, as suggested by previous studies. In addition, induction of the TLR-mediated interferon response was blocked by YopJ, indicating that YopJ also inhibits IRF3 signalling. Examination of the NF-kappaB signalling pathway in detail suggested that YopJ acts at the level of TAK1 (MAP3K7) activation. Further studies revealed a YopJ-dependent decrease in the ubiquitination of TRAF3 and TRAF6. These data support the hypothesis that YopJ is a deubiquitinating protease that acts on TRAF proteins to prevent or remove the K63-polymerized ubiquitin conjugates required for signal transduction. Our data do not directly address the alternative hypothesis that YopJ is an acetyltransferase that acts on the activation loop of IKK and MKK proteins, but support the conclusion that the critical function of YopJ is to deubiquinate TRAF proteins.